DEVELOPMENT OF WOUND HEALING GEL FROM PLANTAGO MAJOR L. EXTRACT - kartini, kartini (Media Pharmaceutica Indonesiana, 2016)
As a conclusion, the reasons why P. major is selected to be developed as wound healing products are: This plant is widely distributed, thus the collection of raw material for production scale is easier. Since a long time ago people around the world have believed empirically that P. major can be used in many ailments, one of them is wound.Many researchers have proved scientifically that P. major has contribution in wound healing process. One of the chemical compounds of P. major responsible for wound healing mechanisms has been recognized, i.e. aucubin. This plant contains varies chemical compounds that supposed synergistically support the wound healing activity of âactive compoundâ.